2018
DOI: 10.1002/ps.5146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endophytic fungi in Mongolian pine on the selection behavior of woodwasp (Sirex noctilio) and the growth of its fungal symbiont

Abstract: Some species of the host endophytic fungi had a significant negative effect on the growth and development of woodwasps, which could be useful in the monitoring and effective management of woodwasps. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 48 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Previous studies have found that the species of endophytic fungi are closely related to the health level of trees 43 . In this study, Trichoderma , Aspergillus were the dominant genera of endophytes (Table 2 ) as reported in different host plants 44 – 46 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have found that the species of endophytic fungi are closely related to the health level of trees 43 . In this study, Trichoderma , Aspergillus were the dominant genera of endophytes (Table 2 ) as reported in different host plants 44 – 46 .…”
Section: Discussionmentioning
confidence: 98%
“…4 ). The results show that the fungal community structure is greatly affected by tree health conditions 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research showed that C. globosum completely inhibited the mycelial growth of Amylostereum areolatum 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to superior adaptability and survivability, A. niger is ubiquitous in nature, including in terrestrial soil (Xie et al, 2006), ocean (Li et al, 2016;Uchoa et al, 2017), the Arctic (Singh et al, 2011), and space. It also occupies a wide spectrum of habitats in plants and animals such as herb (Shreelalitha and Sridhar, 2015;Manganyi et al, 2018), shrub (Kaur et al, 2015;Liu et al, 2016), tree (Soltani and Moghaddam, 2014;Wang et al, 2019), lichen (Elissawy et al, 2019), shrimp (Liu et al, 2013;Fang et al, 2016), and marine sponge (Takano et al, 2001;Hiort et al, 2004). A. niger strain grows well in various media with different carbon sources, including glucose, bran, maltose, xylan, xylose, sorbitol, and lactose (Toghueo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%